A new Masdevallia (Pleurothallidinae) from the Huanuco region in Peru - Dalström, Stig; Deburghgraeve, Guido; Ruíz Pérez, Saúl (Lankesteriana: International Journal on Orchidology, 2023)
A new Masdevallia from the cloud forests of Huanuco, Peru, is described and illustrated. It is morphologically similar to what is considered to be its closest relatives, the sympatric Masdevallia fenestralis and Masdevallia fenestrellata, but differs from both by the lack of translucent fenestrations (“window-like” areas) near the base of the sepals, and by the presence of distinct external ridges of the sepals.